PERLINDUNGAN PRIVASI DATA ONLINE - Rendi Rizky Trianda (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
The development of information and communication technology, one of which is the internet (interconnection networking). Protection of personal data privacy if it is not regulated in a law and regulation can result in losses for someone due to the dissemination of personal information. This study aims to analyze the protection of personal data privacy in a comparative law perspective. This study uses the literature study research method. Data collection techniques by collecting several previous studies as a reference for answering the importance of using Shopee among students, the latest features of Shopee that make it easier for consumers to use it and the reasons students choose to buy and sell online at Shopee, as well as supporting data. as supports such as newspapers, magazines, articles, e-books from the internet, image data and graphics according to the topic. The purpose and focus of this research is to find out the nature of legal protection of personal data as a right to privacy and forms of legal protection of personal data as a right to privacy in Indonesia. The result of this research is that the essence of legal protection of personal data as a right to privacy is a citizen's constitutional right. Indonesia does not yet have statutory regulations which form the legal basis for the protection of personal data